2012
DOI: 10.1371/journal.pone.0047237
|View full text |Cite
|
Sign up to set email alerts
|

Parapapillary Atrophy: Histological Gamma Zone and Delta Zone

Abstract: BackgroundTo examine histomorphometrically the parapapillary region in human eyes.Methodology/Principal FindingsThe histomorphometric study included 65 human globes (axial length:21–37 mm). On anterior-posterior histological sections, we measured the distance Bruch's membrane end (BME)-optic nerve margin (“Gamma zone”), BME-retinal pigment epithelium (RPE) (“Beta zone”), BME-beginning of non-occluded choriocapillaris, and BME-beginning of photoreceptor layer. “Delta zone” was defined as part of gamma zone in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
138
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(150 citation statements)
references
References 21 publications
(18 reference statements)
8
138
0
Order By: Relevance
“…23 Beta-and gamma-PPA areas were mostly associated with different covariates, and not related to each other, reinforcing the hypothesis that they could be the result of different physiological mechanisms. [11][12][13][14] Gamma-PPA was significantly associated with oval discs and oblique configuration of the border tissue of Elshnig, similar to what was previously reported. 13,14 Kim et al 32 documented development of PPA and progressive tilting of the optic disc in children with myopic shift, demonstrating that PPA might be caused by globe elongation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…23 Beta-and gamma-PPA areas were mostly associated with different covariates, and not related to each other, reinforcing the hypothesis that they could be the result of different physiological mechanisms. [11][12][13][14] Gamma-PPA was significantly associated with oval discs and oblique configuration of the border tissue of Elshnig, similar to what was previously reported. 13,14 Kim et al 32 documented development of PPA and progressive tilting of the optic disc in children with myopic shift, demonstrating that PPA might be caused by globe elongation.…”
Section: Discussionsupporting
confidence: 88%
“…2,3 Although both the prevalence and size of beta-PPA is increased in glaucoma, [4][5][6] these features are also observed in myopia [7][8][9] and with increasing age. 4,8,10 Recent histologic 11 and spectraldomain optical coherence tomography (OCT) [12][13][14][15][16] imaging studies proposed a new classification for beta-PPA, dividing it into two subsets that are indistinguishable by clinical examination: an area with intact Bruch's membrane, still termed beta-PPA, and an area lacking Bruch's membrane, termed gamma-PPA. Recent studies showed that gamma-PPA had a higher association with myopia, [11][12][13]15 and could represent anatomical changes resulting from globe elongation, whereas beta-PPA with intact Bruch's membrane has a higher association with glaucoma, 11,14,15,17 reduced choroidal volume, 17 and older age, 13,16,17 possibly representing degenerative changes.…”
mentioning
confidence: 99%
“…These findings agree with a recent histomorphometric study in which gamma zone and delta zone of the parapapillary region were significantly associated with axial length but not with glaucoma, whereas beta zone of the parapapillary region was significantly associated with glaucoma but not with axial length. 11 The macular Bruch's membrane defect in highly myopic eyes would be second to the primary hole in Bruch's membrane as the inner layer of the optic nerve head, as the optic nerve head can be considered to be a two-layered structure: an inner hole in Bruch's membrane and an outer hole in the sclera (i.e., the optic nerve scleral canal). The primary Bruch's membrane hole present in all eyes allows the passage of the retinal ganglion cell axons out of the eye, and the passage of the large retinal vessels in and out of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,11,13,14 The question arises as to which reasons led to the development of an MBMD in highly myopic eyes. One may assume that the myopic enlargement of the globe mainly occurring posterior to the equator is associated with a stretching of Bruch's membrane parallel to the thinning of the sclera.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to an overhanging of the Bruch's membrane in the nasal region of the optic nerve head or optic disc (as also shown clinically by optical coherence tomography) and to an absence of the Bruch's membrane at the temporal disc border. 21 The absence of the Bruch s membrane in the parapapillary region has recently been examined and measured in histomorphometric studies. The region without the Bruch's membrane (and correspondingly, without retinal pigment epithelium and choriocapillaris) has been called parapapillary gamma zone.…”
Section: Optic Nerve Headmentioning
confidence: 99%